Molecular Docking Analysis of Compounds in Coleus blumei Leaves as Potential Antibiotics Against Methicillin-Resistant Staphylococcus aureus - Sukmawaty, Eka; Amanda, Sabilla Suryaning; Hafsan; Nur, Fatmawati; Pratiwi, Afryanti (Fakultas Farmasi, Universitas Surabaya, 2025)
This study investigated the potential of phytochemical compounds from Coleus blumei leaves as anti-Methicillin-Resistant Staphylococcus aureus (MRSA) candidates through a validated molecular docking and absorption-distribution-metabolism-excretion-toxicology (ADMET)-based screening approach. The ligand structures were energy-minimized using MMFF94 followed by PM7 to obtain stable conformers prior to docking. Protein targets consisted of PBP2a and the extracellular antibiotic-sensing domain of MecR1 (benzylpenicilloyl- and oxacilloyl-acylated forms), both of which play central roles in the mecA-mediated resistance pathway of MRSA. Docking simulations were performed using AutoDock Vina v1.2.7 and validated through redocking of co-crystallized ligands, yielding RMSD values <2.0 Å. Among the eight tested compounds, Hexahydro-3H-1[2’-trifluoromethyl]-6’[4’’-trifluoromethylphenyl]- exhibited the strongest binding affinities, surpassing reference β-lactam antibiotics and demonstrating key interactions with residues involved in allosteric activation of PBP2a and ligand sensing in MecR1. ADMET predictions further supported its drug-likeness and safety profile, although experimental confirmation remains necessary. These findings highlight this compound as a promising anti-MRSA lead candidate and underscore the need for subsequent in vitro and in vivo evaluations to substantiate its mechanistic and therapeutic potential.